Gastro-protective effect of capsaicin in Anguilla anguilla (Linneus, 1758): evidence from an experimental study on gastric bags. - DENARO, Maria Gabr.; CARUSO G; GENOVESE L. (2006)
An experimental, macroscopical, study was undertaken in european eel (Anguilla anguilla) to assess the gastro-protective effect of capsaicin, the active component contained in pepper. Gastric bags were prepared from specimens of Anguilla anguilla and used for in vitro study of the ability of capsaicin to recover ulcers induced by aspirin or ethanol. Gastric ulcers were experimentally induced and comparison was made with the same experiment repeated in presence of capsaicin at different concentrations (10-6, 10-5, 10-4 mol/l). Macroscopical observations showed that capsaicin at low doses (10-6 mol/l) was effective in repairing the mucosal layer injured, thus proving in vitro its protective effect on the gastrointestinal tract of this fish species. Moreover, the similar physiological behaviour of the protective effect found between our study and other in vivo studies performed on rats supported the possibility of using the gastro-intestinal tract of eel as a model substrate for pharmacological and toxicological studies